2013
DOI: 10.1021/ci300445e
|View full text |Cite
|
Sign up to set email alerts
|

3D Molecular Descriptors Important for Clinical Success

Abstract: The pharmacokinetic and safety profiles of clinical drug candidates are greatly influenced by their requisite physicochemical properties. In particular, it has been shown that 2D molecular descriptors such as fraction of Sp3 carbon atoms (Fsp3) and number of stereo centers correlate with clinical success. Using the proteomic off-target hit rate of nicotinic ligands, we found that shape-based 3D descriptors such as the radius of gyration and shadow indices discriminate off-target promiscuity better than do Fsp3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 51 publications
3
64
0
Order By: Relevance
“…[c] Diastereomeric ratios were determined by 1 Having identified optimal reaction conditions ( Table 1, Entry 8), we set out to explore the substrate scope of this chemistry with respect to other dienal substrates (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[c] Diastereomeric ratios were determined by 1 Having identified optimal reaction conditions ( Table 1, Entry 8), we set out to explore the substrate scope of this chemistry with respect to other dienal substrates (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…These structures are exceptionally interesting because an increase in saturation, as measured by the fraction of sp 3 carbon atoms, and a high number of asymmetric centers in the molecular structures, tend to correlate with clinical success. [1] In terms of making natural products, synthetic strategies based on the formation of nonaromatic chiral polycycles from simple building blocks has been harnessed by several research groups. [2] In particular, the marriage of oxidative dearomatization and asymmetric catalysis in a single vessel has emerged as an attractive strategy to increase molecular complexity from simple and readily-introduced functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…26,30 Numerous studies on virtual screening targeting nAChRs have also been reported by others in recent years. 31−41 Most of these studies have used molecular docking approach.…”
Section: ■ Introductionmentioning
confidence: 86%
“…5 In addition, shape-based 3D descriptors such as the radius of gyration (ROG) and shadow indices (Shadow Xlength, SXL) explicitly describe the compactness and flatness of a compound, and therefore represent an efficient way to evaluate the propensity of a compound to advance from clinical trials to the market. 15 Although predictions based solely on physicochemical properties should be taken with care, drug candidates successfully advancing to clinical trials tend to share the following properties: SXL ≤ 16.09; ROG < 4.11; F sp 3 ≥ 0.42. Additionally, the chance of a preclinical candidate passing through the different clinical trial stages was also evaluated by the quantitative estimate of the drug-likeness (QED) descriptor.…”
Section: Molecular Shape and "Drug-likeness" Properties Of Azadkpsmentioning
confidence: 99%